LEARNING EFFECTIVELY IN THE REAL AND VIRTUAL CLASSROOM - Mihaela Aurelia ŞTEFAN; Oprea-Valentin BUȘU (Universitaria Publishing House, Craiova, 2024)
The present study aims to draw attention to a possible systemic model of academic learning. The objectives pursued were: a) investigating the opinion of students-future teachers regarding the academic learning process; b) building and applying an experimental program focused on the development of academic learning competence; c) conducting an opinion poll regarding the role of the experimental Program. The experimental program designed and applied, based on a holistic approach to learning, had in mind the following directions: a) motivationalattitudinal support; b) action at the cognitive and metacognitive level; c) practicing the skills and affirming the desirable behavior, more precisely, putting the students in a situation. The research undertaken allowed us to collect data that we then subjected to quantitative and qualitative analysis. Following the results obtained, we were able to formulate directions regarding the development of students' competence to learn effectively.